Solar Energy Potential in Nepal and Global Context - Adhikari, Krishna R.; Gurung, Shekhar; Bhattarai, Binod K. (Journal of the Institute of Engineering, 2014)
Solar radiation is the best option and cost effective energy resources of this world from 21st century onwards. In this study monthly, seasonal and annual variation of global solar insolation at Biratnagar, Lukla, Kathmandu, Pokhara, of the year 2007 to 2012, Jumla of the year 2011 to 2012 and Simikot 2011/2012 were carried out. The study has shown the variation of global solar insolation with month, season, year, atmospheric condition, and altitude of the site concerned. The maximum value of monthly, seasonal, and yearly global solar insolation was reported at Jumla whereas the minimum monthly, seasonal, and yearly global solar insolation were observed at Kathmandu. From the observation the abundant solar irradiation in Nepal shows encouraging atmosphere for solar farming venture in near future relating to energy management for Nepal. DOI: http://dx.doi.org/10.3126/jie.v9i1.10675 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 95–106